2010
DOI: 10.1016/j.ijhcs.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Telling the story of older people e-mailing: An ethnographical study

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 45 publications
5
63
0
2
Order By: Relevance
“…A study that supports the first hypothesis reported that the use of e-mail -the most used medium of communication by Brazilian older adults on the internet 9 -can bring greater social well-being and comfort to older adults. Sayago & Blat 20 conducted an ethnographic study about the use of e-mail with 388 Spanish older adults, and found the following benefits: closer interaction with friends and relatives; feeling of digital inclusion and broader integration into the modern society; feeling of accomplishment and higher self-esteem; and reinforcement of the traditional methods of communication.…”
Section: ) (Continuation) Tabela 4 -Razões De Prevalência (Rp) Brmentioning
confidence: 99%
“…A study that supports the first hypothesis reported that the use of e-mail -the most used medium of communication by Brazilian older adults on the internet 9 -can bring greater social well-being and comfort to older adults. Sayago & Blat 20 conducted an ethnographic study about the use of e-mail with 388 Spanish older adults, and found the following benefits: closer interaction with friends and relatives; feeling of digital inclusion and broader integration into the modern society; feeling of accomplishment and higher self-esteem; and reinforcement of the traditional methods of communication.…”
Section: ) (Continuation) Tabela 4 -Razões De Prevalência (Rp) Brmentioning
confidence: 99%
“…From this study, they concluded that to encourage elder people into the computing world, we have to develop an easy user interface while taking into account the above mentioned characteristics. Sayago and Blat (2010) undertook a research on designing a better e-mail systems and interactive technologies for elder people (above 65 years old). They analyzed needs and cognitive difficulties of elder people and grouped the interaction barriers of an email systems for elder people into five categories.…”
Section: Designing User Interface For Elder Usersmentioning
confidence: 99%
“…Table 3 shows key points of user interface design for children. (Sayago and Blat, 2010) Solving elders' problems by creating an easy layout, using large font, proper icons and easy terms. (Wirtz et al, 2009) In older ages some cognitive characteristics such as intelligence, information processing and memory changes.…”
Section: Designing User Interface For Childrenmentioning
confidence: 99%
“…Additionally, Sayago and Blat, in studying a group of older Web users, found that many Web-related tasks carried out by members of the group were done collaboratively, involving two or more people sharing one computer [33]. The involvement of an assistive technology, such as a screen magnifier, may reduce -or be perceived as reducing -the usability of the computer for the partner without impairments, adversely affect the social quality of the collaborative activity.…”
Section: Attitude To Assistive Technologymentioning
confidence: 99%